Analyses of infrequent (quasi‐decadal) large groundwater recharge events in the northern Great Basin: Their importance for groundwater availability, use, and management. Issue 10 (11th October 2016) - Masbruch, Melissa D.; Rumsey, Christine A.; Gangopadhyay, Subhrendu; Susong, David D.; Pruitt, Tom
Abstract: There has been a considerable amount of research linking climatic variability to hydrologic responses in the western United States. Although much effort has been spent to assess and predict changes in surface water resources, little has been done to understand how climatic events and changes affect groundwater resources. This study focuses on characterizing and quantifying the effects of large, multiyear, quasi‐decadal groundwater recharge events in the northern Utah portion of the Great Basin for the period 1960–2013. Annual groundwater level data were analyzed with climatic data to characterize climatic conditions and frequency of these large recharge events. Using observed water‐level changes and multivariate analysis, five large groundwater recharge events were identified with a frequency of about 11–13 years. These events were generally characterized as having above‐average annual precipitation and snow water equivalent and below‐average seasonal temperatures, especially during the spring (April through June). Existing groundwater flow models for several basins within the study area were used to quantify changes in groundwater storage from these events. Simulated groundwater storage increases per basin from a single recharge event ranged from about 115 to 205 Mm 3 . Extrapolating these amounts over the entire northern Great Basin indicates that a single large quasi‐decadal recharge event could result in billions of cubic meters of groundwater storage. Understanding the role of these large quasi‐decadal recharge events in replenishing aquifers and sustaining water supplies is crucial for long‐term groundwater management. Key Points: Five large quasi‐decadal recharge events were identified in the northern Great Basin Recharge events could result in billions of cubic meters of recharge in the northern Great Basin Recharge events replenish groundwater storage lost during drought and groundwater pumping